2012
DOI: 10.1590/s0101-20612012005000056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified clays on the structure and functional properties of biofilms produced with zein

Abstract: The purpose of this study was to evaluate changes in the structure and some functional properties of biofilms added with modified clays (Cloisite® 15A and Cloisite® 30B) prepared by the casting method. The analysis of the microstructure of the films, scanning electron microscopy (SEM), Optical microscopy (MO), and Infrared Spectroscopy (FTIR) indicated that the addition of clay in the films resulted in the formation of a heterogeneous microstructure, microcomposite or tactoid. Due to the formation of a microco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
3
0
3
Order By: Relevance
“…The presence of globular deposits or pores was verified by the presence of rounded structures, showing that a continuous filmogenic matrix did not form. This observation was also reported in zein films [12,19,[34][35][36] , chitosan film [37] and pectin [38] .…”
Section: Scanning Electron Microscopysupporting
confidence: 81%
See 1 more Smart Citation
“…The presence of globular deposits or pores was verified by the presence of rounded structures, showing that a continuous filmogenic matrix did not form. This observation was also reported in zein films [12,19,[34][35][36] , chitosan film [37] and pectin [38] .…”
Section: Scanning Electron Microscopysupporting
confidence: 81%
“…It has been used to develop functional biodegradable packaging [5] , packages with antimicrobial agents [6][7][8][9] , packaging for periodontal biomaterials and substrates for cell culture [10] . Studies with zein have been carried out in respect to the regeneration of osseous tissues [11] , with nanoparticles used to improve the mechanical properties of films [12,13] and edible film to increase the shelf life of pears [14] and macadamia [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The Figure 3 showed that the film was in the form of membranes with some less dense regions noticeable in the darker areas, with pores and small cracks. Monterrey-Quintero and Sobral [22] and Tavares et al [23] suggested that the black spots indicated in Figure 3 were microbubbles embedded in the matrix or spaces occupied by glycerol before the drying process. Spada et al [24] suggested that cracks in the structure may be related to sample storage conditions, drying by using forced convection or high temperatures.…”
Section: Film Microstructurementioning
confidence: 98%
“…Colaborando com sua potencialidade, a adição de nanopartículas aos filmes exibe propriedades superiores, como maior resistência, maior estabilidade térmica e oxidativa, melhor barreira a gases e à água (TAVARES et al, 2012). A incorporação de ácidos graxos, a exemplo do ácido oleico, como plastificante, produz filmes flexíveis, homogêneos, transparentes e de boa aceitação (XU et al, 2012;FORATO et al, 2013).…”
Section: Formas De Extração De Zeína Do Milhounclassified
“…Quando proveniente de fonte natural, é biodegradável em curto período de tempo (VILLADIEGO et al, 2005;FORATO et al, 2013). A formação de novos materiais biodegradáveis substitui o uso de plásticos oriundos de polímeros sintéticos, derivados do petróleo, prejudiciais ao meio ambiente por resistirem à degradação (TAVARES et al, 2012).…”
Section: Introductionunclassified